Handbook of Scientology - Lewis, James R.; Hellesøy, Kjersti (Brill handbooks on contemporary religion, 2017)
The 'Handbook of Scientology' brings together a collection of fresh studies of the most persistently controversial of all contemporary New Religions. In recent years, increasing scholarly attention has been directed at the Church of Scientology, resulting in a small tsunami of new scholarship. We have finally reached a point in time where a book on Scientology need not restrict itself to basics. Thus, for example, the historical chapters in the present volume are not really aimed at providing elementary facts on Scientology's background, but, rather, focus on understanding how the Church of Scientology developed over the years. In short, the Handbook of Scientology will provide a wealth of new information on a topic that one might otherwise have thought exhausted